Peran Budaya Dalam Pembentukan Hubungan Manusia, Tempat Dan Lingkungan - Almunawar, Arizal; Agustina, Aas; Nur Wulandari, Ika; Raihana, Shafa; Lilis (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2023)
ABSTRACT Culture is a fundamental aspect in shaping human relationships with place and the environment. Culture is not only seen as a product of human creation, but also as a system of values, norms, and symbols that guide behavior in managing and interpreting living space. This article aims to analyze the role of culture in bridging human interactions with their environment, both physical and social. Through a literature review, it was found that culture has a significant influence on how humans adapt, utilize resources, and maintain ecosystem sustainability. Concrete examples of culture's role are evident in local wisdom, such as sasi in Maluku, awig-awig in Bali, or the forbidden forest tradition in Sumatra, which have proven effective in preserving the environment. On the other hand, the currents of globalization and modernization often shift local cultural values, resulting in environmental problems and the loss of place identity. This study emphasizes that the integration of local culture in environmental management has strategic urgency, especially in facing the challenges of climate change and ecosystem degradation. Thus, culture is not merely a legacy, but a vital instrument in creating a harmonious relationship between people, place, and the environment.